Mechanical response and deformation mechanisms of porous PZT95/5 ceramics under shock-wave compression. Issue 2 (February 2021) - Jiang, Zhaoxiu; Gao, Guangfa; Xiong, Xun; Wang, Yonggang
Abstract: A series of plate impact experiments were performed to investigate the shock response of porous PZT95/5 ceramics. Based on the measured free surface velocity profiles, the influences of impact velocity and porosity on the shock response of porous PZT95/5 ceramics were explored. Then, the shock response of porous PZT95/5 ceramics was numerically simulated by using the discrete element method (DEM) based on flat-joint bonded contact model to analyze the microscopic deformation mechanisms. The simulation results of the free surface velocity profiles agreed well with experimental results. The macroscopic deformation process of porous PZT 95/5 ferroelectric ceramics under shock-wave compression can be divided into four stages: elastic deformation, cracks spread deformation, void collapse deformation and Hugoniot state. The microscopic deformation mechanisms of porous PZT95/5 ceramics under shock-wave compression could be mainly attributed to the nucleation and growth of large numbers of shear cracks and tension cracks around voids, as well as the collapse of voids in ceramics.